Crianças nas redes sociais: controle parental e design centrado na criança em plataformas digitais - Rocha, Beatriz Matos dos Reis (2025)
The dramatic expansion of digital technologies has fostered a growing integration between the virtual and physical worlds, impacting everyday life and especially children, whose use of the Internet is becoming increasingly common, from play activities to searching for school information. However, this presence of children online is fraught with risks, including exposure to inappropriate content, threats to privacy, cyberbullying and manipulation by digital platforms. Therefore, there is an urgent need to protect children's rights in the digital environment by ensuring safe access and preserving their privacy. This dissertation examines the impact of digital platforms on children's daily lives, focusing on the role of parental controls and child-friendly design as tools to promote safe and inclusive experiences. Based on a qualitative and exploratory analysis, the study examines three relevant platforms: Instagram, TikTok, and YouTube Kids, and examines their parental control tools, usability, and alignment with children's rights. The research discusses the challenges associated with children's use of technology, including the risks of exposure to inappropriate content, manipulative practices, and developmental impacts. It shows that while there are protective mechanisms such as private accounts and content filters, parental mediation is essential to complement these tools and promote dialogue and awareness. The dissertation also questions the exclusive delegation of responsibility for parental control to platforms, given their commercial interests. Finally, it highlights the need for a design that prioritizes children's needs and co-responsibility between families, platforms and society to create a more ethical and safer digital environment that is aligned with children's full development. This study contributes to the reflection on the role of design and parental mediation in the protection and digital inclusion of children